Estudio de factibilidad para la ampliación de la empresa 'Solo Babys', Atuntaqui, Imbabura - Males Irua, Cristian Ricardo (2023)
The objective of this research work is to prepare a feasibility study for the expansion of the Solo Baby's Atuntaqui-Imbabura company\; This study has generated a reason that the sales area has registered an increase in the demand for the children's clothing segment since the year 2022, however, the factory and its current installed capacity cannot satisfy the market requirements due to the limited volume of production. Consequently, it is necessary to carry out the respective study to determine the needs of the organization and design the proposal. For this study, the deductive and synthetic analytical research methods were improved, with a non-experimental design with a transversal axis, since the process of collecting and analyzing the information obtained through the interview applied to the select group of representatives of the groups was carried out. of interest. Furthermore, it is complemented by a mixed approach because it is assembled by certain quantitative and qualitative data and details. And finally, the scope of the project is descriptive in that it exposes the commercial and productive situation, as well as the weaknesses, strengths and opportunities. The proposal has been developed in three important stages that are: the prolonged market study through which the supply and unsatisfied demand are identified, the technical study through which the choice of machinery, materials and essential instruments in the production process was made. production, the optimal size of the company, the redistribution of the plant\; and finally, there is the financial analysis that contributes to demonstrate the feasibility of expanding the Solo Babys factory.